PP.63 Shoulder Dystocia – A Risk Management Point of View. (26th April 2013) - Burrell, C; Kropiwnicka, Z; Frisby, C
Abstract : Background: Shoulder dystocia remains a common cause of litigation in obstetrics. The RCOG Shoulder Dystocia Guideline (2005) recommends auditing all cases of shoulder dystocia to improve training and patient care. Aim: This retrospective cohort study reviewed maternal and fetal complications for all cases of shoulder dystocia from July 1, 2008–Dec 31, 2010 at a large University Teaching Hospital in the UK. Method: Cases were collected from the Operating Theatre, Special Care Baby Unit, Delivery Suite and Risk Management Registries. Results: There were 292 cases (∼1%) of shoulder dystocia [primigravida (n = 100), and multiparous (n = 192)]. The overall total [Group 1] (n = 292 mean birth-weight 3.979 kg ± 0.475; the Instrumental Delivery [Group 2] (n = 94) mean birth-weight 3.937 kg ± 0.486; and the Instrumental Delivery in Theatre [Group 3] (n = 28) mean birth-weight 4.036 kg ± 0.577. In group 3, a Consultant was present in theatre 19/28 (67.86%). FETAL COMPLICATIONS: SCBU Admission (n = 17) – 5.82% Macrosomia > 4.5 kg (n = 33) – 11.30% Erbs Palsy & Bone Fracture (n = 6) – 2.05% Stillbirth (n = 1) MATERNAL COMPLICATIONS: Postpartum Haemorrhage >1000 mls (n = 20) – 6.85% 3 rd Degree Tear (n = 22) – 7.53% & [4 th degree Tear (n = 1)] Severe Shoulder Dystocia Delivery head-to-body interval ≥ 5 mins (n = 12) – 4.10% Delivery Required ≥ 3 Manoeuvres (n = 34) – 11.64% Conclusion: The Risk Management team had a robust proforma with standardise documentation to identify, investigate (Serious Incident Reporting) and include all shoulder dystocia cases in the monthly maternity dashboard. All Erbs palsy/fractures cases had outpatient Paediatric and Physiotherapy followed-up. All staff must attend mandatory training involving shoulder dystocia drills.